THE EXPERIENCE OF LONELINESS AS A FACTOR OF INCREASING THE PERSONAL POTENTIAL OF STUDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In recent years, the phenomenon of loneliness has attracted psychological scientists as one of the pressing problems of our modern society. Statistics show that during the pandemic, the tendency to loneliness increased in young people compared to older people. The problem of loneliness is widely studied in foreign psychology, where it is studied on the basis of various theories, concepts, approaches, positions, directions. This article presents the results of our research on the mechanisms of perception of loneliness and the impact of this phenomenon on the personal potential of students in Uzbekistan. As the personal potential of a person characterizes the inner physical and spiritual energy of a person, his active position aimed at creative self-expression and self-realization.